Gene Regulation and Arteriosclerosis: Are Developmental Programs Reactivated in Vascular Disease? - Patterson, Cam (Thrombosis and Haemostasis, 1999)
The molecular mechanisms regulating the development of vascular diseases such as atherosclerosis remain poorly understood at present. Similarities between genetic programs observed during the course of vascular disease with those observed during vascular development suggest that developmental processes are recapitulated in vascular disease. The earliest event in vascular development is the differentiation of endothelial cells from their mesodermally-derived hamangioblastic precursors. The receptor for vascular endothelial growth factor, KDR/flk-1, plays a critical role in these earliest stages of vascular development. During development and in the adult, expression of this receptor is restricted to vascular endothelial cells and their immediate precursors. We have therefore endeavored to determine the transcriptional events regulating KDR/flk-1 expression, with the hope of gaining insight into processes of vascular development that might also be important in vascular diseases of the adult.
Keywords: Angiogenesis; gene regulation; atherosclerosis; proliferation